Bullying behavior among students - Maria Ulfah; Erni Gustina (Institute of Advanced Engineering and Science, 2020)
This study aimed to investigate whether communication patterns, peers’ involvement and gender different can be the predictors of adolescent bullying behavior. This study involved 193 adolescents of grade 8 and 9 with the most adolescents of 14 years old who had filled in questionnaires. The results showed the prevalence of adolescent involvement in bullying which was 62.69%. Parental communication patterns have an OR = 1.64 (95% CI=0.87-3.09). Peers involvement in bullying behavior (OR=1.92; 95% CI=1.01-3.66). Adolescent girls were more involved in bullying behavior (59.59%) compared to adolescent boys (OR=3.32; 95% CI=1.69-6.54). Poor parental communication patterns, peers influence negatively predict to the bullying behavior in adolescent. Bullying is higher in boys than girls where as boys has a greater chance of bullying than girls. Therefore, bullying intervention programs are needed in schools.